(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
Chromium has now become a threat for environment and health due to its extensive use in leather tanning in Bangladesh. Considering easy availability and cost effectiveness, rice husk and leftover tea waste biomass were used as biosorbent for chromium (III) absorption. Through batch experiment, absorption efficiencies at different parameters (pH, chromium concentration, absorbent dosage, exposer time) were determined and measured by FAAS. The results showed that efficiencies of left over tea waste and rice husk were 87.14% and 85.71% respectively. Our study revealed that 7.5 gm/L biosorbent works best to absorb 0.5 mM chromium(III) solution under 45-60 minute exposer in room temperature at pH 4.0- 5.0. At natural condition, 72% and 78.4% chromium were absorbed from the raw tannery effluent by rice husk and tea waste respectively. FT-IR studies indicated the functional groups (O-H, C-H, C=C, C=O, C≡C and C≡N) might be involved in the sorption of Cr (III) onto leftover tea waste and rice husk biomass. The findings indicate that these biosorbents could be employed in the removal of Cr (III) from aqueous solutions and industrial effluents. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (2), 193-198